PRODUKTIVITAS PADI VARIETAS INPARI 33 DAN FAKTOR YANG MEMPENGARUHINYA DI KABUPATEN KARANGANYAR PROVINSI JAWA TENGAH - Wahyu Adhi Saputro; Restie Novitaningrum; Ringgo Ismoyo Buwono (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
Central Java Province is one of the national food buffer provinces. Central Java province has good soil fertility so that the agricultural sector can become the leading sector in this province. One of the commodities cultivated in the Karanganyar Regency is rice with the Inpari 33 variety. This study aims to determine the analysis of the productivity of Inpari 33 rice in Karanganyar Regency and the production factors that affect the productivity of Inpari 33 rice varieties. This study was conducted in 3 villages, namely Jati Village. , Suruh Kalang Village and Jetis Village in Jaten District, Karanganyar Regency in the second planting season, namely April-July. The sample was taken as many as 90 farmers from the 3 villages intentionally with the consideration that farmers grow rice varieties inpari 33 and are active in farmer group membership. The data analysis method used in this research is the analysis of productivity and production functions of Cobb-Douglass. Based on the results of the study, it can be seen that the average production of Inpari 33 rice owned by farmers in Karanganyar Regency is 1,367.14 kg of dry milled grain. Farmers' rice productivity reached a value of 4,538.08 kg per hectare. Factors that affect rice productivity are land area, number of seeds, urea fertilizer, SP36, NPK, organic fertilizers, solid pesticides and the number of workers.